Comparison of Pandan Leaf Extract (Pandanus Amaryllifolius) Using Ethanol and N-Hexane to The Content of Bioactive Compounds - Burhana, Nanda Azizah; Akbar, Moch. Fatchul; Putri, Ambar Salsabilla; Agustina, Eva; Lusiana, Nova; Purnamasari, Risa (International Conference on Sustainable Health Promotion, 2023)
The content of bioactive compounds in pandan leaves is used as traditional medicine. One of the utilization efforts is done by maceration extraction. This extraction involves the presence of a solvent. The choice of solvent is a success factor in the maceration extraction process. This study aims to determine the effect of different types of solvents on the content of bioactive compounds and phenolic content of pandan leaf extract. The research method was carried out through maceration extraction using ethanol and n-hexane solvents. Determination of compound content using qualitative phytochemical tests and quantitative tests of phenolic content using UV-Vis spectrophotometry and identification of compounds using FTIR instruments. The results showed that pandan leaf extract positively contained alkaloids, saponins, steroids, and phenolics. The total phenolic content was 12.207 mg/g GAE in ethanol and 10 mg/g GAE in n-hexane. Also, the FTIR test of ethanol solvent shows the O-H bond spectrum in the 3300 region, C=C in the 1650 region, and C-O in the 1100 region. Meanwhile, in n-hexane solvent a C=O bond spectrum is formed in the 1700 region. Both solvents form a C-H bond in the 2900 region. The spectrum formed indicates the presence of phenolic compounds in pandan leaves.